The US National Efforts to Counter Domestic Terrorism: Progress and Controversy - Hendroy, Faruq Arjuna (Global Strategis, 2018)
The article examines the increasing domestic terrorism threat within the U.S. borders and how the U.S. government responded to it. The robust maneuver of the U.S. ledcoalition in the Middle East to coercively hunt down the terrorist groups does not fully stop them from posing the threat. Ironically, the terrorist groups direct their attacks to the U.S. homeland through their small networks. It is not difcult to build networks in the U.S. homeland, since the the advance of millennium technology enables them to radicalize people from long distance. The U.S. surely concerns about the increasing number of terrorist attacks within its borders, that it recently issued a set of national counter-terrorism strategy combining both coercive and soft approach. However, the approval of discriminatory and controversial travel ban policy was believed to hamper the existing national strategy, mistarget the main causes, and create new problems.